1979
DOI: 10.1104/pp.64.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in the Cell Walls of Ripening Apple and Pear Fruit

Abstract: Ultrastructural changes in the cell walls of "Calville de San Sauveur" apples (Mahn sylvestris Mi) and "Spadona" pear (Pyrs conunws L.) frit were folowed during rpening. In apple, structural alteratons in cell walls became apparent at advanced stages of softening and showed predominantly disolution of the middle lamella. In pears softening was also associated with the dissolutio of the middle lamella, and in addition a gradual disintegration of fibria material throughout the cell wall. In fully ripe fruit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
61
0
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(75 citation statements)
references
References 16 publications
10
61
0
4
Order By: Relevance
“…Pear cell walls contained also high quantities of lignin (212e232 mg/g). The high concentrations of glucose, xylose and lignin reflected the presence of lignified cell walls rich in xylans and cellulose, typical of EC: (À)-epicatechin, PCA: procyanidins, DPn: average degree of polymerization of procyanidins, CQA: 5 0 -caffeoylquinic acid, Flavonols: sum of flavonols, Total: sum of polyphenols, n.d.: not detected, Pooled SD: pooled standard deviation, ns: not significant (P > 0.05), ***: P < 0.0001, **: P < 0.01, *: P < 0.1. stone cells (Ben-Arie, Kislev, & Frenkel, 1979;Martin-Cabrejas, Waldron, Selvendran, Parker et al, 1994). Le Bourvellec et al (2013) detected more galacturonic acid and less xylose in the AIS from the flesh of William pears.…”
Section: Composition Of Alcohol Insoluble Solids (Ais)mentioning
confidence: 99%
“…Pear cell walls contained also high quantities of lignin (212e232 mg/g). The high concentrations of glucose, xylose and lignin reflected the presence of lignified cell walls rich in xylans and cellulose, typical of EC: (À)-epicatechin, PCA: procyanidins, DPn: average degree of polymerization of procyanidins, CQA: 5 0 -caffeoylquinic acid, Flavonols: sum of flavonols, Total: sum of polyphenols, n.d.: not detected, Pooled SD: pooled standard deviation, ns: not significant (P > 0.05), ***: P < 0.0001, **: P < 0.01, *: P < 0.1. stone cells (Ben-Arie, Kislev, & Frenkel, 1979;Martin-Cabrejas, Waldron, Selvendran, Parker et al, 1994). Le Bourvellec et al (2013) detected more galacturonic acid and less xylose in the AIS from the flesh of William pears.…”
Section: Composition Of Alcohol Insoluble Solids (Ais)mentioning
confidence: 99%
“…Fruit that soften significantly at the fully ripe stage typically have CWs that appear swollen, both in planta and in vitro, and this ripeningassociated wall swelling correlates with pectin solubilization (27,28). CWs were isolated from LR and RR AC and transgenic fruit and suspended in water.…”
Section: Fig 5 Pathogen Growth Is Reduced In Liquid Cultures Contaimentioning
confidence: 99%
“…This has led to the suggestion that certain hydrolytic enzymes are responsible for the dissolution of the middle lamella as well as for the degradation of the cell wall itself, thereby leading to a general loss of cohesion of the tissue, perceived as softening. This model is supported by anatomical work that demonstrated the breakdown of middle lamella polymers (Ben-Arie et al, 1979), by numerous studies characterizing the ripening-related changes in cell wall polymers (Gross and Wallner, 1979;Ahmed and * Corresponding author; e-mail jmlabavitch@ucdavis.edu; fax 1-916 -752-8502. Labavitch, 1980;Gross, 1984), and by studies that demonstrated increases in the activities of some putative cell wall polysaccharide hydrolases during ripening (Hobson, 1968;Tucker et al, 1982;Brady et al, 1983;Pressey, 1989; for review, see Fischer and Bennett, 1991).…”
mentioning
confidence: 56%